Scalability of information centric networking using mediated topology management. (April 2015) - Alzahrani, Bander A.; Reed, Martin J.; Riihijärvi, Janne; Vassilakis, Vassilios G.
Abstract: Information centric networking is a new concept that places emphasis on the information items themselves rather than on where the information items are stored. Consequently, routing decisions can be made based on the information items rather than on simply destination addresses. There are a number of models proposed for information centric networking and it is important that these models are investigated for their scalability if we are to move from early prototypes towards proposing that these models are used for networks operating at the scale of the current Internet. This paper investigates the scalability of an ICN system that uses mediation between information providers and information consumers using a publish/subscribe delivery mechanism. The scalability is investigated by extrapolating current IP traffic models for a typical national-scale network provider in the UK to estimate mediation workload. The investigation demonstrates that the mediation workload for route determination is on a scale that is comparable to, or less than, that of current IP routing while using a forwarding mechanism with considerably smaller tables than current IP routing tables. Additionally, the work shows that this can be achieved using a security mechanism that mitigates against maliciously injected packets thus stopping attacks such as denial of service that is common with the current IP infrastructure.